Assessment of Antidepressant Activity of Phosphodiesterase-4 Inhibitor Drotaverine in Swiss Albino Mice: Antidepressant activity of Drotaverine - Srivastava, Vivek; Yadav, Prabhat Kumar; Kaushik, Rudrakshri; Goel, Kapil (Iranian Journal of Pharmaceutical Sciences, 2026)
Depression is a mental health disorder characterized by profound feelings of sadness and a sense of hopelessness. It is a life-threatening disorder and approximately 20% of world’s population is affected by depression. Drotaverine is used as an anti-spasmodic drug. It is structurally like Papaverine. It selectively inhibits the phosphodiesterase-4 (PDE-4) enzyme. The antispasmodic medication drotaverine was utilized as a test drug in this investigation, and its effects as an antidepressant were examined. Compared to the standard drug imipramine used for depression therapy, it has fewer negative effects. For a variety of behavioral (in vivo) and non-behavioral (in vitro) investigations, we have employed Swiss Albino mice. The Forced Swim Test, Tail Suspension Test, and Elevated Plus Maze Model Test are three behavioral models that were applied to estimate the antidepressant influence of drugs. The non-behavioral techniques of MAO-A and MAO-B inhibition were employed to assess the antidepressant action of medications. We have also conducted an antioxidant investigation using the Nitric Oxide Scavenging Assay and Glutathione (GSH) estimate. Additionally, histopathological investigations and protein measurements were carried out. The outcomes were noteworthy and excellent. The test drug has shown considerable efficacy and promise as an antidepressant agent in the Tail Suspension Test (TST) (*p<0.05), Elevated Plus Maze Model Test (EPM) (*p<0.05), as well as Forced Swim Test (FST) (*p<0.01). The results were compared to the reference drug. The test medication had little to no effect on MAO inhibition, in accordance with assessment of MAO-A alongwith MAO-B. Nitric oxide (*p<0.05), glutathione (GSH) estimation (****p<0.0001), and total protein estimation (****p<0.0001) all showed considerable scavenging effects. The histopathological results provided a quick overview of the effects of both experimental and prescription medications, as well as the alterations to the cerebellar granular neurons, Purkinje cells, and cerebrum cell bodies. This points to the drug’s protective function in the brain.